Vietnam : 2001 Article IV Consultation and First Review Under the Poverty Reduction and Growth Facility and Request for Waiver and Modification of Performance Criteria-Staff Report; Staff Statement; Public Information Notice; News Brief; and Statement by the Executive Director for Vietnam. (IMF Staff Country Reports; Country Report ;, 2002)
This paper assesses Vietnam's 2001 Article IV Consultation, First Review Under the Poverty Reduction and Growth Facility (PRGF), and a Request for Waiver and Modification of Performance Criteria. Economic performance has been positive so far in 2001, under the first-year PRGF-supported program. Despite slowing exports, real GDP growth has been relatively robust, inflation subdued, and the external position has strengthened. All but two of the end-June quantitative benchmarks and performance criteria were observed. The authorities are taking corrective steps and pursuing a policy agenda aimed at sustaining growth and protecting macroeconomic stability.